PENGARUH SUPLEMENTASI SINBIOTIK TERHADAP PROFIL GLIKEMIK DAN LIPID PADA PASIEN DIABETES MELITUS TIPE 2: Sebuah Tinjauan Sistematis pada Studi Randomisasi Acak - Ansyori, Achmad Rifky; Zefianto, Zefianto; Riena, Nadya Ratna; Novalina, Fellen (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a glucose homeostasis disorder characterized by chronic hyperglycemia caused by insulin resistance. It is believed that this condition is associated with intestinal bacteria dysbiosis that potentially worsens T2DM progressivity. A number of experimental studies have recommended synbiotic supplementation, based on the principle of intestinal microbe regulation, as nutrition therapy for T2DM. This systematic review evaluates the effect of synbiotic supplement on T2DM patients’ glycemic and lipid profile. Methods: Articles published from 2014 to 2021 were searched with a number of search engines: PubMed, ResearchGate, Google Scholar, and Elsevier. This systematic review aims to evaluate the effect of synbiotic supplement on T2DM patients’ glycemic and lipid profile. Discussion: Eighty randomized control trials (RCTs) met the inclusion criteria to be analyzed qualitatively in this systematic review. The quality of each included study was evaluated with Cochrane’s Risk of Bias (ROB-2). Overall, in comparison to the control (placebo) group, the intervention group that received synbiotic supplementation showed a more significant decrease in fasting glycemic and HbA1c level. T2DM patients also appeared to experience improvement in lipid profile (decrease in cholesterol, triglyceride, and low density lipoprotein cholesterol (LDL-C), along with increase in high density lipoprotein cholesterol (HDL-C)) after receiving synbiotic supplementation. In addition, synbiotic supplementation is evaluated as safe to be consumed by T2DM patients with minimal side effects. Conclusion: The available evidence demonstrates the potential use of synbiotic supplementation as a nutrition therapy for T2DM treatment. Keywords: glycemic profile, lipid profile, synbiotic, type 2 diabetes mellitus.